Serial blood lactate concentrations in systemically ill dogs - Stevenson, Connie K (Veterinary clinical pathology, 2007)
BACKGROUND: Lactate concentration often is quantified in systemically ill dogs and interpreted based on human data. To our knowledge, there are no published clinical studies evaluating serial lactate concentrations as a prognostic indicator in ill dogs